Global leaders in Islamic finance : industry milestones and reflections - Alim, Emmy Abdul (Singapore : Wiley, 2014)
Interviews with the professionals driving the rapid global growth of Islamic finance Though the modern Islamic finance system has existed for more than forty years, its size and influence in the banking industry has expanded massively in just the last decade. This book looks at Islamic finance from the perspective of the experts shaping the industry, including some of the founders of the first Islamic banks-Haj Saeed Lootah, His Royal Highness Prince Mohamed Al Faisal Al Saud, and Sheikh Saleh Abdullah Kamel-as well as other professionals who have greatly influenced the industry.
The Islamic Economist/Activist / Khurshid Ahmad -- The very first mover / Saeed Bin Ahmed Al Lootah -- The well of influence / Prince Mohamed Al Faisal Al Saud -- Steadily spreading the blessings / Saleh Abdullah Kamel -- The systematic rise of a national industry / Mahathir Mohamad and the Malaysian Story -- The Islamic Economist / Abbas Mirakhor -- The global standard-setter / Rifaat Ahmed Abdel Karim -- The scholar / Sheikh Nizam Yaquby -- The lawyer / Michael JT McMillen -- The equity capital market man / Rushdi Siddiqui -- More than the sum of Its parts: forty years of Islamic finance.
Includes bibliographical references and index.
Print version record.
Keywords: Banks and banking -- Islamic countries; Bankers -- Islamic countries -- Interviews; Bankers; Banks and banking; Islamic countries; Electronic books; Interviews